A Collection of Brain Sections of "Euthanasia" Victims: The Series H of Julius Hallervorden. Issue 4 (December 2017) - Wässle, Heinz
Highlights: Investigates "euthanasia, " the killing of mentally ill patients during the Nazi-era. Brain tissue slides of euthanasia victims collected by Julius Hallervorden. The continued abuse of brain tissue slides for neuropathological research and teaching after World War II. Abstract: Julius Hallervorden, a distinguished German neuropathologist, admitted on several occasions that he had received some five hundred brains of "euthanasia" victims from the Nazi killing centres for the insane. He investigated the brains in the summer of 1942; however, their traces were subsequently lost. The present study shows, that the Series H, which was part of the Hallervorden collection of brain sections in the Max Planck Institute for Brain Research, comprises the brain sections of the above mentioned five hundred euthanasia victims. The provenance of 105 patients could be reconstructed and 84 are for sure euthanasia victims. Most of them were killed in Bernburg or in Sonnenstein-Pirna. Hallervorden used the brain sections of Series H until 1956 for his studies and never publicly regretted this abuse of the brains of euthanasia victims.